Breast Cancer Management with Melanie E Royce: BOLERO-4 Phase II trial of first-line everolimus plus letrozole in ER+, HER2- advanced breast cancer. (August 2016) - Royce, Melanie E
Melanie E Royce* speaks to Roshaine Wijayatunga, Managing Commissioning Editor : Melanie E Royce is a Professor in the Department of Internal Medicine, Division of Hematology/Oncology at the University of New Mexico Comprehensive Cancer Center (UNM CCC) in Albuquerque, NM, USA. She received her PhD and MD degrees at the University of Cincinnati, Ohio; then completed her Internal Medicine Residency at Yale University-New Haven Hospital in Connecticut and Medical Oncology Fellowship at The University of Texas MD Anderson Cancer Center in Houston, Texas where she subsequently joined the faculty until she moved to Albuquerque, to be one among the first batch of oncology faculty recruits to help establish an National Cancer Insititute (NCI)-designated CCC in the state of NM.  At UNM CCC, she serves as the Director of the Multidisciplinary Breast Cancer Clinic and Programs and Co-Leader of the Women's Cancer Program. She is engaged in the care of breast cancer patients and is the Principal Investigator for several breast cancer clinical trials at the UNM CCC. On a national level, she serves on the Breast Cancer Committee of the Southwest Oncology Group and the NCI Breast Oncology Local Disease Task Force. Beyond breast cancer, she has a wider involvement in clinical research being the Director of the Clinical Protocol and Data Management of the UNM CCC and the contract Principal Investigator for the NM Minority/Underserved NCI Community Oncology Research Program, a grant that enhances patient and provider access to NCI-led clinical trials. The NM NCI Community Oncology Research Program in partnership with the NM Cancer Care Alliance, a state-wide clinical trials consortium, facilitates access to an expansive array of clinical trials to virtually all cancer patients statewide.